The values of contemporary music in the context of the content school education - Mirosław Grusiewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: This paper is devoted to contemporary music, its value and its presence in schools of general education. Research Aim: The aim is to show that many phenomena of the contemporary music culture, even songs which are commonly regarded as a part of pop culture, have some artistic value and should be included in school curricula.  Evidence-based Facts: The general practice of school music education is based on the Polish concept of music education, which was developed in the 70s of the 20th century. One of the alternatives promoted by some of the media is the so-called pop culture education. The participants of the educational activity rely on the joint measures of art, leaving them on the margins of their artistic interests. Summary: The article not only critically assesses school practice based on the Polish concept of music education and some assumptions and demands of pop-cultural education, but also proposes alternative solutions. The overriding idea is the necessity to base education (which should be the practice of music rather than learning about music) on contemporary works with undeniable artistic values. Looking for such works, the author relies on his own classification, in which the basic categories are 'subtlety', 'originality, uniqueness' and 'the creator's intention'.